Energy and centrality dependence of deuteron and proton production in Pb + Pb collisions at relativistic energies - Antičić, Tome (Array, 2004)
The transverse mass mt distributions for deuterons and protons are measured in Pb + Pb reactions near midrapidity and in the range 0<mt-m<1.0 (1.5) GeV/c2 for minimum bias collisions at 158A GeV and for central collisions at 40 and 80 A GeV beam energies. The rapidity density dn/dy, inverse slope parameter T and mean transverse mass mt derived from mt distributions as well as the coalescence parameter B2 are studied as a function of the incident energy and the collision centrality. The deuteron mt spectra are significantly harder than those of protons, especially in central collisions. The coalescence factor B2 shows three systematic trends. First, it decreases strongly with increasing centrality reflecting an enlargement of the deuteron coalescence volume in central Pb + Pb collisions. Second, it increases with mt. Finally, B2 shows an increase with decreasing incident beam energy even within the SPS energy range. The results are discussed and compared to the predictions of models that include the collective expansion of the source created in Pb + Pb collisions